Road preference survey for commuting trips from to workplace - Ameey Azleenda, Abd Rahim (2008)
A road is an identifiable route, way or path between two or more places. Road is typically smoothed, paved and otherwise prepared to allow easy travel for the road user. Transportation, traffic system and road network are the most important element which can influence level of development of the country. The objectives of this study are to identify the existing residential locations of UMP’s staff and their preferred commuting route to UMP and to determine their reasons in choosing the current residential locations and the preference commuting route to UMP. The roads involve is in between Jalan Kuantan – Gambang [FR2] and East Coast Expressway (LPT). At the moment, Jalan Kuantan – Gambang [FR2] is getting congested especially during AM & PM peak hours. On the other hand, East Coast Expressway (LPT) is under utilized due to a number of reasons. This study is basically carrying out based on that phenomenon and both roads had been selected as study area of this research. In this study, data collection is carrying out through e-survey, where the questionnaires had been distributed through e-mail to all staffs and lecturers of UMP. This kind of methodology is one kind of new method that being applied in final year project in UMP. The results show that, majority of the respondents prefers to choose Jalan Kuantan – Gambang [FR2] as their preferred road for commuting trips to workplace, which represent 89% of total percentage whereas 11% of respondents prefer to use East Coast Expressway (LPT) to go to workplace. The main reasons of Jalan Kuantan – Gambang [FR2] user is the location of their residential location, different with East Coast Expressway (LPT) user, as they more considering the factor of safety and comfortness of their daily journey to workplace. Poor accessibility of the highway from a main road may become the main reasons for the respondents not to use East Coast Expressway (LPT) as their daily commuting route to UMP. The action must be taken by responsible parties to plan and develop the new interchange of the highway in order to increase the numbers of road user. In the same time, it will reduce the congestion level of Jalan Kuantan – Gambang [FR2]